Levels of Antiepileptic Drugs and the Ketogenic Diet - J Gordon Millichap (Pediatric Neurology Briefs)
Introduction of the ketogenic diet did not change the plasma levels of antiepileptic drugs in an open study of 51 children (mean age 6.6 years) with refractory epilepsy studied at Karolinska University Hospital, Stockholm, Sweden.